2015
DOI: 10.1007/s11060-015-1932-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis from melanoma: the prognostic value of varying sites of extracranial disease

Abstract: Patients with brain metastasis from melanoma have poor outcomes. Radiation is used both for prognostic and symptomatic value. We aimed to further clarify the role of stereotactic radiosurgery (SRS) and whole brain radiotherapy (WBRT) as well as the prognostic implication of various sites of extracranial disease. The records of 73 consecutive patients treated at the University of Rochester Medical Center for brain-metastatic melanoma from January 2004 to October 2013 were reviewed. The median overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Another selection bias arises from the effect of protocol eligibility criteria [12]. Most CTs included in our study strictly prohibited enrollment of patients with advanced disease, such as those with brain metastasis, an adverse prognostic factor for several cancers [18][19][20]. However, the two study groups had comparable proportions of metastatic location and burden, corroborating our hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…Another selection bias arises from the effect of protocol eligibility criteria [12]. Most CTs included in our study strictly prohibited enrollment of patients with advanced disease, such as those with brain metastasis, an adverse prognostic factor for several cancers [18][19][20]. However, the two study groups had comparable proportions of metastatic location and burden, corroborating our hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…The HRs for each prognostic factor extracted from 31 observational studies are summarized in Table S9 , meta-HR are summarized in Table 3 , and forest plots provided in Figures S7–S15 ( 1 , 27 , 47 , 48 , 50 , 64 89 ). Meta-analysis suggested elevated lactate dehydrogenase (LDH) levels, male gender, BRAF wild-type, increased number of intracranial metastases, presence of active extracranial metastases, lower Karnofsky Performance Scale (KPS), and larger MBM volume were significantly associated with worse prognosis in patients with MBM.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a prospective study of patients (median KPS 70) reported similar survival for a 60 Gy 6-week and 40-Gy 3-week course with less steroid dependency associated with HRT (68). The same group then showed equivalence in survival and QoL between 25 Gy/5 fractions and 40 Gy/15 fractions for elderly and/or frail patients (91).…”
Section: Patients With Poor Performance Statusmentioning
confidence: 88%